PERTUMBUHAN Nannochloropsis sp. YANG DIKULTUR PADA SKALA SEMI-MASSAL DAN MASSAL DI UPTD BPBALP TELUK BUO, PADANG, SUMATERA BARAT - Virnando, Irvan; Bareta, Ainun Rohmawati; Lisna, Lisna; Pratama, Giri; Afkar, Zawil; Cahyono, Hari; Putri, Rahayu Dian Eka (Mantis Journal of Fisheries, 2025)
Natural feed plays a crucial role as a primary nutrient source that is easily digested and suitable for the physiological needs of larvae during early life stages. Nannochloropsis sp. is widely used as a main natural feed for larvae of various aquaculture commodities, making its stable and high-quality availability essential for hatchery success. This study aimed to evaluate Nannochloropsis sp. culture techniques at semi-mass and mass scales and to determine cell density as an indicator of feed quality. The study employed direct observation during the culture period and descriptive analysis of cell density and water quality. Culture procedures at both scales included tank preparation, seawater filling, inoculation, cell density measurement, and harvesting, with differences only in tank size and inoculum volume. Results showed that peak cell density on day five reached 42,326,000 cells/mL in the semi-mass scale and 39,400,000 cells/mL in the mass scale, followed by a decline on day six. The study concludes that the Nannochloropsis sp. culture technique applied at UPTD BPBALP Teluk Buo is effective in supporting phytoplankton supply for hatchery operations.